Isolation by elevation: genetic structure at neutral and putatively non-neutral loci in a dominant tree of subtropical forests, Castanopsis eyrei. - Miao-Miao Shi; Stefan G Michalski; Xiao-Yong Chen; Walter Durka (PLoS ONE, 2011)
The distribution of genetic diversity among plant populations growing along elevational gradients can be affected by neutral as well as selective processes. Molecular markers used to study these patterns usually target neutral processes only, but may also be affected by selection. In this study, the effects of elevation and successional stage on genetic diversity of a dominant tree species were investigated controlling for neutrality of the microsatellite loci used.Diversity and differentiation among 24 populations of Castanopsis eyrei from different elevations (251-920 m) and successional stages were analysed by eight microsatellite loci. We found that one of the loci (Ccu97H18) strongly deviated from a neutral model of differentiation among populations due to either divergent selection or hitchhiking with an unknown selected locus. The analysis showed that C. eyrei populations had a high level of genetic diversity within populations (A(R) = 7.6, H(E) = 0.82). Genetic variation increased with elevation for both the putatively selected locus Ccu97H18 and the neutral loci. At locus Ccu97H18 one allele was dominant at low elevations, which was replaced at higher elevations by an increasing number of other alleles. The level of genetic differentiation at neutral loci was similar to that of other Fagaceae species (F(ST) = 0.032,  = 0.15). Population differentiation followed a model of isolation by distance but additionally, strongly significant isolation by elevation was found, both for neutral loci and the putatively selected locus.The results indicate higher gene flow among similar elevational levels than across different elevational levels and suggest a selective influence of elevation on the distribution of genetic diversity in C. eyrei. The study underlines the importance to check the selective neutrality of marker loci in analyses of population structure.